Socio-Economic Disparities in Pediatric Viral Gastroenteritis: A Comparative Study of Clinical Outcomes and Management in Hospitalized Children with Rotavirus, Adenovirus, and Norovirus Infections - Ioana Arbanas; Gabriela Coja; Alice Bilotta; Raluca-Ileana Lixandru; Oana Patran; Laura Bleotu; Oana Falup-Pecurariu (Children, 2025)
Background: Acute viral gastroenteritis (AVG) still has an impact on children under 5 years old in developing countries. In Romania, vaccination against Rotavirus is not included in the National Immunization Program. Children from poor social backgrounds represent 48% of the patients hospitalized in Children’s Clinical Hospital of Brasov. The use of antibiotics in Romania is high. Methods: The retrospective study enrolled 1054 children, 0–48 months of age, hospitalized in the Emergency Clinical Hospital for Children Brasov between January 2022–December 2023, for Rotavirus, Adenovirus or Norovirus acute gastroenteritis. Children presenting nosocomial infections were excluded. All children that have met the previously mentioned criteria, presenting positive stool samples (immunochromatography method) for Rotavirus, Adenovirus or Norovirus were included in the study. Results: Out of 1054 cases of AVG 782 (74.2%) were due to Rotavirus, 196 (18.5%) to Adenovirus and 76 (7.3%) to Norovirus. A total of 477 (45.3%) patients came from poor social backgrounds and 577 (54.7%) children from good social backgrounds. Rotavirus infection was equally prevalent in both groups (p < 0.35). Children from poor social backgrounds presented an average age of 11 months (SD ± 9; range 14 days–48 months) and a hospitalization average of 5.86 days (SD ± 3.67; range 1–22 days) compared to the others, who presented an average of 21 months (SD ± 15; range 26 days–48 months) and hospitalization average of 5.20 days (SD ± 2.51; range 1–18 days) (p < 0.01; p < 0.01). Severe dehydration presented 267 children from poor settings (56%) and 186 (17.6%) received antibiotics, compared to the other group—224 children (38.8%) with severe dehydration and 216 (20.4%) receiving antibiotics. The most used antibiotic for both groups was Ceftriaxone (53.9% and 57.6% of all AVG). Conclusions: Rotavirus is the leading AVG cause. Children from poor backgrounds were younger, more dehydrated, hospitalized longer.